Techno-economic assessment of electrolytic hydrogen in China considering wind-solar-load characteristics - Lu, Gang; Yuan, Bo; Gu, Zhongfan; Chen, Haitao; Wu, Cong; Xia, Peng (Frontiers in Energy Research, 2023)
Hydrogen production by electrolysis is considered an essential means of consuming renewable energy in the future. However, the current assessment of the potential of renewable energy electrolysis for hydrogen production is relatively simple, and the perspective is not comprehensive. Here, we established a Combined Wind and Solar Electrolytic Hydrogen system (CWSEHs), considering the influence of regional wind-solar-load characteristics and transmission costs to evaluate the hydrogen production potential of 31 provincial-level regions in China in 2050. The results show that in 2050, the levelized cost of hydrogen (LCOH) in China's provincial regions will still be higher than 10 ¥/kg, which is not cost-competitive compared to the current hydrogen production from fossil fuels. It is more cost-effective to deploy wind turbines (WT) than photovoltaic (PV) in areas with similar wind and solar resources or rich in wind resources. Wind-solar differences impact LCOH, equipment capacity configuration, and transmission cost composition, while load fluctuation significantly impacts LCOH and electricity storage (ES) configuration. In addition, the sensitivity analysis of 11 technical and economic parameters showed differences in the response performance of LCOH changes to different parameters, and the electrolyzer conversion efficiency had the most severe impact. The analysis of subsidy policy shows that for most regions (except Chongqing and Xizang), subsidizing the unit investment cost of WT can minimize LCOH. Nevertheless, from the perspective of comprehensive subsidy effect, subsidy cost, and hydrogen energy development, it is more cost-effective to take subsidies for electrolysis (ELY) equipment with the popularization of hydrogen.